ANALISIS WACANA AKUN FACEBOOK HUMOR POLITIK TERKAIT PILKADA DKI JAKARTA TAHUN 2017 - Rizki Amalia Yanuartha; Laila Kholid Alfirdaus (Universitas Kristen Satya Wacana, 2020)
The development of technology and communication marked a change in the generation of political communication. The interesting thing in it is the realization of political participation through cyber technology accompanied by the emergence of hate speech discourse. This study aims to explain the discourse formed and identify various forms of political messages on the Humor Politik Facebook account related to the DKI Jakarta Regional Election in 2017. The method used is the critical discourse analysis method of Norman Fairclough. Limitation of research on the final goal does not generally look at social changes that occur. The results of the analysis from 218 memes, linguistically and socio-culturally indicate that the text contains more forms of satire and criticism on two pairs of candidates, namely number 1 (Agus Harimurti Yudhoyono – Sylviana Murni) and 3 (Anies Rasyid Baswedan – Sandiaga Salahudin Uno) governors and deputy governors of DKI Jakarta in 2017. While the text of support to the candidate pairs number 2 (Basuki Tjahaja Purnama – Djarot Saiful Hidayat). The text contains hate speech totaling 23 memes with forms of provocation and insults in the context of religion, ethnicity, race, sexuality, culture and personality. The production of political messages is a model of communal participation. Seen from the identification of the form and production of messages including the unconventional participation model. While political activities include political participation in the form of electoral activity by showing patterns of participation that express political preferences and indirectly also showing patterns of campaign participation or promotion of certain candidates. The form of political messages also leads to image packaging and tends towards neutralization. Through social media, political participants can express their opinions in the form of self-satire, criticism, or support. But it also requires a selective and critical attitude in interpreting every political message. Considering the use of social media today encourages more participation and impacts on the continuation of democracy.